Risk Factors for Antenatal Depression among Women Attending Tertiary Care Hospitals in Coastal Part of South India - Nithin Kumar; Darshan Bhagwan; Nidhi Singh; Monisha D'Souza; Unnikrishnan Bhaskaran; Rekha Thapar; Mithra Prasanna; Vaman Kulkarni; Holla Ramesh (Medsci Publications, 2017)
Introduction: Antenatal depression has often been overlooked and under-diagnosed throughout the world, especially in developing nations like India. The study was conducted to assess the prevalence of antenatal depression among pregnant women in South India and to identify associated risk factors. Methods: A cross sectional study was conducted over seven months on 201 pregnant women in Mangalore. A semi structured questionnaire using Edinburgh Postnatal Depression Scale (EPDS) was used. Data was analyzed using SPSS version 11.5. Results: 201 pregnant ladies were evaluated for antenatal depression. Majority women (52.7%) belonged to the age group of 26-30 years. Using EPDS we found that 10.9% women were progressing towards antenatal depression. The risk of developing antenatal depression was statistically significant among the women (21.1%) who were married before 20 years of age (p= 0.027), who were multi-gravida (p=0.002) and who were facing pressure from in-laws (p<0.05). Conclusion: Need for clinical efforts to focus on early recognition and effectively managing antenatal depression by screening, thus preventing progression to postpartum depression and its ill effects.